Social participation and mortality: does social position in civic groups matter?. (December 2016) - Ishikawa, Yoshiki; Kondo, Naoki; Kondo, Katsunori; Saito, Toshiya; Hayashi, Hana; Kawachi, Ichiro
Abstract Background Social participation is known to predict longevity. However, little is known about the effect of social participation according to an individual's position in civic groups. We evaluated the influence of social position on mortality, using data from a large cohort of Japanese older adults (the AGES cohort). Methods Of 14, 804 individuals aged 65 years and older enrolled in the AGES, 14, 286 individuals were followed up for approximately 5 years from 2003 to 2008. We performed inverse probability of treatment weighted (IPTW) Cox proportional hazards regression with multiple imputation of missing values to compute hazard ratios (HR) for all-cause mortality according to the individual's position in the community organization(s) to which they belonged. We examined participation in the following civic groups: neighborhood association/senior citizen club/fire-fighting team, religious group, political organization or group, industrial or trade association, volunteer group, citizen or consumer group, hobby group, and sports group or club. The values for IPTW were computed based on demographic variables, socioeconomic status, and self-reported medical condition. Results During 22, 718 person-years of follow-up for regular members of community groups and 14, 014 person-years of follow-up for participants in leadership positions, 479 deaths and 214 deaths were observed, respectively. Relative to regular members, crude HR for all-cause mortality for occupying leadership positions (e.g. president, manager, or having administrative roles) was 0.72 (95 % CI:0.62–0.85). The IPTW-HR was 0.88 (95 % CI: 0.79–0.99) for participants occupying leadership positions. Conclusions Holding leadership positions in community organization(s) may be more beneficial to health than being regular members.